Chan, Anita, Richard Madsen y Jonathan Unger. Chen Village. The Recent History of a Peasant Community in Mao’s China. Berkeley, University of California Press, 1984, viii + 293 pp. - Cornejo Bustamante, Romer (Estudios de Asia y África, 1985)
-